Association Between Body Mass Index and Low Back Pain Among Students at the Faculty of Medicine, Pelita Harapan University - Thiono, Jeskry; Suryadinata, Neneng (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Low back pain (LBP) is the most common musculoskeletal complaint and the largest contributor to the burden of disability in the world. One of the risk factors for LBP is having a higher body mass index (BMI). Although the relationship between BMI and LBP in the age group susceptible to LBP has been widely studied, the relationship in the young adult age group is still under-researched. Meanwhile, several studies report that lifestyle changes that occur during the COVID-19 pandemic might lead to an increasing number of overweight obese sufferers, including in the young adult age group. Given the context, this research aims to determine the relationship between BMI and LBP in UPH Medical Faculty (FK UPH) students during the COVID-19 pandemic.Method: A cross-sectional method of unpaired categorical comparative analytical study design was conducted with a population of 414 medical students. Data were collected by an online survey of BMI measurement and the Nordic Musculoskeletal Questionnaire. Statistical analysis was done using SPSS Statistics with Chi-squared or Fischer's exact method.Result: The study involved a sample of 372 people with 188 people (50.5%) being LBP sufferers. Most of the sample belongs to the category of BMI < 23 kg/m2, which is 215 people (57.8%).Conclusion: The result from this research concludes that there is no significant relationship between BMI and LBP in FK UPH students during the COVID-19 pandemic (P = 0.420); significant relationships were found between LBP with gender (P = <0.001) and smoking habit (P = 0.022).